Biological status of blue swimming crab population (Portunus pelagicus) in Estuarine Water at Langsa City - Nurdian Novita Sari; Suri Purnama Febri; Andika Putriningtias; Teuku Fadlon Haser; Rachmawati Rusydi; Hanisah Hanisah; Suraiya Nazlia; Ika Rezvani Aprita (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Many factors encourage the exploitation of the blue swimming crab in the estuarine water of Langsa City. Therefore, maintaining crab populations in nature through fishing regulation becomes an important effort. Evaluation of the biological aspects of the blue swimming crab population the estuarine waters of Langsa City has the main role in the arrangement of regulation. This study aimed to determine the biology of the blue swimming crab population in the estuarine waters of Langsa City. This research was carried out in August 2022 in the estuarine waters of Langsa City. The method used was the survey method. The crab samples were taken randomly from the crab fishermen as much as 10% of the catch. Sampling once a week at 2 different location points for 1 month. The results showed that the relationship between carapace width and weight of male and female blue swimming crabs (Portunus pelagicus) had a negative allometric growth pattern because of the value of b 3, namely 1.22 and 1.21. The sex ratio of blue swimming crabs was not 1:1 or unbalanced. Gonadal maturity of male crabs was highest in level I, meanwhile the female could achieve the gonadal maturity in level V. During the research, the water quality of estuarine waters was in optimum condition.Keywords:Blue swimming crabBiological aspectEstuarinePopulation